Evaluating the superiority of honey over silver sulphadiazine dressing in shortening healing duration of burn injury: an evidence-based case report (Medical Journal of Indonesia, 2013)
Background: Burn injury is a global health problem associated with major morbidity and mortality. Honey has long been used in wound management due to its ability to accelerate healing rates and prevent infection. This study is conducted to evaluate the efficacy of honey dressing in shortening healing duration of burn injury compared to silver sulphadiazine (SSD). Methods: A PubMed and Proquest database search was conducted to identify relevant studies. The studies were then appraised and ranked based on their validity, importance, and level of evidence. Results: The two studies appraised in this paper supported the supremacy of honey against SSD in shortening healing duration. However, the individual quality of studies involved was low. Conclusion: Honey is an alternative treatment in shortening burn wound healing duration. Further studies are needed to support clinical application of this conclusion. (Med J Indones. 2013;22:243-7. doi: 10.13181/mji.v22i4.608) Keywords: Burn injury, healing duration, honey, silver sulfadiazine